De novo gene birth - Van Oss, Stephen Branden; Carvunis, Anne-Ruxandra (PLoS genetics, 2019)
A 2009 report identified the first three de novo human genes, one of which is a therapeutic target in chronic lymphocytic leukemia [45]. Since this time, a plethora of genome-level studies have identified large numbers of orphan genes in many organisms (Table 1), although the extent to which they arose de novo remains debated. Phylogenetic trees are limited by the set of closely related genomes that are available, and results are dependent on BLAST search criteria [48]. Because it is based on sequence similarity, it is often difficult for phylostratigraphy to determine whether a novel gene has emerged de novo or has diverged from an ancestral gene beyond recognition, for instance following a duplication event. [...]the discovery of de novo gene birth has also led to a questioning of what constitutes a gene, with some models establishing a strict dichotomy between genic and non-genic sequences, and others proposing a more fluid continuum (see below). [...]it remains debated whether duplication and divergence or de novo gene birth represent the dominant mechanism for the emergence of new genes [63, 65, 73, 75–77], in part due to the fact that de novo genes are likely both to emerge and to be lost more frequently than other young genes (see below).